Multisystemic Impairments in 93 Chinese Patients With Myotonic Dystrophy Type 1 - Li, Mao; Wang, Zhanjun; Cui, Fang; Yang, Fei; Wang, Hongfen; Huang, Xusheng (Frontiers in Neurology, 2020)
Background: Myotonic dystrophy type 1 (DM1) is an autosomal dominant neuromuscular disease characterized by muscle weakness and multisystemic impairments, which significantly impact the quality of life. There is currently an increasing consensus on the necessity of a multidisciplinary assessment in patients with DM1, to improve the management of the disease. Methods: To analyze the prevalence and pairwise relationships between various organs involved, we performed a retrospective study by reviewing demographic and clinical information of DM1 patients including age, disease duration, clinical history, muscular impairment rating scale score (MIRS), results of blood biochemistry, electrocardiogram, echocardiography, and ophthalmologic examination. Results: 93 DM1 patients (60 males and 33 females), aged 34.7±12.6 (mean±standard deviation) years were recruited. Of which, two congenital cases were of maternal and paternal inheritance, respectively. In the other 91 patients, cataract was found in 44.1% of patients, followed by hypogonadism (40.8%), frontal balding (40.7%), and cardiac abnormalities (34.5%). Thyroid dysfunction and insulin insensitivity were relatively uncommon. Age (p<0.001) is independently correlated with cataract, and MIRS correlates positively with cardiac abnormalities (p=0.005) and frontal balding (p=0.015). Male patients more frequently had frontal balding (Risk ratio, 3.98; 95% confidence interval, 1.493-10.611) compared with female patients. Male patients with cataract presented more frequent cardiac abnormalities (Risk ratio, 4.40; 95% confidence interval, 1.055-18.358) compared with non-cataract male patients. Hypogonadism in male patients was characterized as decreased testosterone level, accompanied by elevated levels of luteinizing hormone and follicle-stimulating hormone. Conclusions: In Chinese patients with DM1, we conclude that 1) cataract, hypogonadism, frontal balding and cardiac abnormalities are frequently observed; 2) age is an independent indicator to cataract and MIRS is the only predictor for cardiac abnormalities and frontal balding; 3) a positive correlation between ophthalmologic and cardiac impairments in male patients is found; 4) endocrine abnormalities show diverse manifestations and hormone tests are recommended; 5) particular attention should be given to patients with older age and higher MIRS score.